Mdina: Should it be inscribted as a World Heritage Site? - Camilleri, Antonella (2008)
The author strongly believes in the cultural and heritage product which Malta can offer to the tourism industry. Authorities have tried to use this product to reposition Malta from a Sun, Sand and Sea destination to a heritage destination, reducing the seasonality of the tourism sector. However, not everything comes easy, culture and heritage have been neglected for years and these two major assets need substantial planning, development and conservation to achieve badly needed positive results in the tourism industry.